Examining torture : empirical studies of state repression - Lightcap, Tracy; Pfiffner, James P.; SpringerLink (Online service). (New York : Imprint: Palgrave Macmillan, 2014)
This anthology provides readers a portal to new and interesting research on one of the most important and disturbing aspects of repression by modern states: the use of torture.
Keywords: Science; Science, general